Progress Compromised : Social Movements and the Individual in African American Postmodern Fiction - Glenn, John; Glenn, John (Book collections on Project MUSE., 2019)
Introduction -- Unraveling cultural notions: black progress in Colson Whitehead's The intuitionist -- Restless questioning: anguish and the ethos of black struggle in Alice Walker's Meridian -- Resisting consensus